2021
DOI: 10.21037/atm-20-4201
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, inflammation and coagulation status in patients with immunological disease-related chronic cerebrospinal venous insufficiency

Abstract: Background: Immunological disease-related chronic cerebrospinal venous insufficiency (CCSVI) is rarely reported. This study aimed to analyze clinical characteristics, inflammation, and coagulation status in patients with immunological disease-related CCSVI.Methods: Patients with CCSVI were enrolled from 2017 to 2019 and divided into three cohorts based on their immunological disease backgrounds, including groups with confirmed autoimmune disease, with suspected/subclinical autoimmune disease, and with non-immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Fortunately, these patients achieved complete revascularization with adequate anticoagulation [ 26 ]. Our previous study revealed that the majority of patients with CVSS had a history of hypercoagulability, immune inflammation, thrombophilia, or thrombosis [ 27 ]. Although stenting could correct the local stenosis immediately, it could not correct their systemic thrombophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, these patients achieved complete revascularization with adequate anticoagulation [ 26 ]. Our previous study revealed that the majority of patients with CVSS had a history of hypercoagulability, immune inflammation, thrombophilia, or thrombosis [ 27 ]. Although stenting could correct the local stenosis immediately, it could not correct their systemic thrombophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thrombosis often originates from sinus thrombosis; venous thrombosis alone is rare. Various genetic or secondary thrombogenic factors can be the etiology of cerebral venous stenosis, including Factor V Leiden mutation; thrombin G20210A mutation; hyperhomocysteinemia; protein S, protein C, or antithrombin III defect; pregnancy; puerperium; oral contraceptives; obesity; blood disease; infection; trauma; tumor; dehydration; connective tissue disease; nephrotic syndrome; neurosurgery; and COVID-19 related etiology (2)(3)(4)(5)(6)(7)(8).…”
Section: Cerebral Venous Thrombosismentioning
confidence: 99%
“…However, stenting‐related early adverse effects, such as severe headache, intracranial hemorrhage, and restenosis are still completely eradicate, which largely deteriorate clinical outcomes 6,7,9–11,15 . In addition, the inflammatory process may cause restenosis of CVSS resulting in poor outcomes 16,17 …”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 , 9 , 10 , 11 , 15 In addition, the inflammatory process may cause restenosis of CVSS resulting in poor outcomes. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation